PENGARUH PEMBERIAN TERAPI AKTIVITAS KELOMPOK SOSIALISASI (TAKS) TERHADAP INTERAKSI SOSIAL KLIEN GANGGUAN JIWA - Mashuda, Yazid (JURNAL MEDIA KESEHATAN, 2013)
The purpose of this study was to determine the effect of therapy group socialization activities (syntax) of the client's mental disorder of social interaction. This research is a kind of research is pre experimentation with the design of "one group pre-test post-test". Population size used was 41 clients with impaired social interactions, samples taken proporsiv sampling as many as 30 clients with social interaction disorder treatment. The data was collected directly to the treatment group. Data analysis was performed bivariate tests unuvariat and paired T-test α of 5% (one tail). The results showed that the average in get social interaction prior to the therapy group socialization activities 0.3 while the average social interaction therapy clients after done action group socialization activities 3.6. There perbadaan average social interaction before and after therapy and activity groups no significant increase between the average social interaction group activity after therapy than before therapy in the client group activity with impaired social interaction is undergoing treatment in a mental hospital Soeprapto Bengkulu (P value = 0.000).